Failed Justice Of Jamie Wallace In Gluck's Friends With Benefits (2011): A Marxist Approach - Wulandari, Novi Rina (2012)
This study is aimed to show the search of failed justice of Jammie Wallace in Friends with Benefits movie (2011). The objective of this study is to analyze the film based on the structural analysis and based on the Marxist approach to analyze the failed justice in Friends with Benefits. The writer uses Class Struggle major point of Marxist to answer the problem of the study. The study is descriptive qualitative research which data are taken from script and pictures in Friends with Benefits. The technique of analyzing data is descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity. Second, based on the Marxist analysis, Justice is important for any person in life to maintain her rights. Will Gluck wants to convey a moral message that everyone is entitled to get their right. Failure to obtain the right about the one's feeling is oppression mental. Jammie feeling was suppressed by Dylan. In the end, Dylan is already aware strummed the Jammie's feelings.